El testimonio anticipado, la inmediación en los delitos contra la integridad sexual, en la ciudad de Riobamba, primer semestre 2022. - Barba Bonilla, Pamela Marisol (2023)
The present investigation carries out a legal and dogmatic analysis regarding the reception of the anticipated testimony in the Specialized Judicial Unit Against Violence against Women and Members of the Family Nucleus of the Riobamba Canton, within this Unit there are no technical parameters for this diligence to be carried out which directly contravenes the principle of immediacy, thus tipping the balance only in favor of the victim; Ecuadorian legislation, through the principle of immediacy, requires the presence of the judge in the diligence of the anticipated testimony in order to visualize the facts reported by the victims and in turn request the pertinent clarifications, since it is one of the most important means of proof. important to determine the commission of the sexual crime, by not applying the procedural principle of immediacy, the right to legal certainty, effective judicial protection and due process is violated. The investigation is carried out under a mixed approach, allowing the collection of transcendental data on the subject of the proposed investigation, as a result of the investigation it is evident that there is a direct violation of the principle of immediacy in the development of the diligence of the anticipated testimony. Keywords: Gessel Chamber, Sexual crimes, Immediacy, Legal certainty, Anticipated testimony.